2013
DOI: 10.1155/2013/416245
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Annealing Temperature and KCN Etching on the Photovoltaic Properties of Cu(In,Ga)(S,Se)2Solar Cells Using Nanoparticles

Abstract: Cu(In,Ga)S 2 nanoparticles were synthesized by a hot-injection method under a low-vacuum ambience, which were printed and annealed with Se vapor for Cu(In,Ga)(S,Se) 2 solar cells. The Cu(In,Ga)S 2 nanoparticles were around 14 nm, and the stable ink was obtained by dispersing the nanoparticles in hexanethiol. The crystallinity of the Cu(In,Ga)(S,Se) 2 films increased with the increase in annealing temperature. Cu(In,Ga)(S,Se) 2 solar cells with KCN etching after annealing showed better photovoltaic properties t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…By printing CIGS and CZTS nanoparticles with several KCN etchings before annealing, Guo et al showed a 12.0 and 8.4% conversion efficiency, respectively, without the hydrazine method. Our group found a significant difference in the KCN effect before and after annealing . Thinking about the Guo's results, the KCN etching before annealing may remove organic materials between the CuInS 2 nanoparticles .…”
Section: Compound Solar Cells With Bifunction Of Photoabsorption and mentioning
confidence: 70%
See 2 more Smart Citations
“…By printing CIGS and CZTS nanoparticles with several KCN etchings before annealing, Guo et al showed a 12.0 and 8.4% conversion efficiency, respectively, without the hydrazine method. Our group found a significant difference in the KCN effect before and after annealing . Thinking about the Guo's results, the KCN etching before annealing may remove organic materials between the CuInS 2 nanoparticles .…”
Section: Compound Solar Cells With Bifunction Of Photoabsorption and mentioning
confidence: 70%
“…Thinking about the Guo's results, the KCN etching before annealing may remove organic materials between the CuInS 2 nanoparticles . Also, the KCN etching after annealing may remove CuS x on the top surface of CuInS 2 layers . These CIGS (or CZTS) nanoparticles have been synthesized by the hot‐injection method: the sulfur is injected into the metal‐source (Cu‐In‐Ga or Cu‐Sn‐Zn) hot solution of oleylamine (at 250°C) .…”
Section: Compound Solar Cells With Bifunction Of Photoabsorption and mentioning
confidence: 99%
See 1 more Smart Citation
“…These show the positive impact that made by Southeast Asia countries. Thus, besides Malaysia, other Southeast Asia countries also have done researches on CIGS thin‐film solar cells, such as Thailand and Vietnam as can be seen in Tables 9 and 10, respectively [140–143].…”
Section: Researches On Cigs Thin‐film Solar Cell By Southeast Asia mentioning
confidence: 99%
“…There is plethora of chemical methods including a colloidal process [14], solvothermal process [15] and hot injection [16] to synthesize CIGS nanoparticles. But the chemical processes are either time consuming or requires schlenk-line techniques [17].…”
Section: Introductionmentioning
confidence: 99%